Jejunoileal atresias associated with colonic atresia - Hiroshi Hamada; Yoshinori Hamada; Takashi Doi; Mitsugu Sekimoto (Elsevier, 2020)
Colonic atresia (CA) is one of the rarest causes of neonatal intestinal obstruction. The combination of jejunoileal atresia (JIA) and CA is particularly rare. To the best of our knowledge, only 21 cases of JIA associated with CA have been described in the English-language literature. We herein present a case involving a 34-week preterm female infant with bilious vomiting by the first day of life. Laparotomy revealed jejunal gap atresia and ileal gap atresia. In addition, colonic gap atresia was found at the hepatic flexure with a wide mesenteric defect. The JIA and CA appeared to have been caused by a thromboembolic event in the superior mesenteric artery. We also review the 21 previously published cases and discuss the etiologies of the association between JIA and CA.